Influence of water and terpenes on flammability in some dominant Mediterranean species - Alessio, G. A.; Penuelas, J.; Llusia, J.; Ogaya, R.; Estiarte, M.; De Lillis, M. (INTERNATIONAL JOURNAL OF WILDLAND FIRE, 2008)
In the Mediterranean basin, fires are a major concern for forest and shrubland ecosystems. We studied flammability, its seasonality and its relationship with leaf moisture and volatile terpene content and emission in the dominant species of a Mediterranean shrubland and forest in Catalonia ( NE Iberian Peninsula). We measured temperatures and time elapsed between the three flammability phases: smoke, pyrolysis and flame, for four seasons. We sampled twice in spring because of an occasional drought period during this season. Flammability had a significant relationship with leaf hydration, in the shrubland and in the forest. Few and only weak correlations were found between terpene content and flammability. In the future, arid conditions projected by climatic and ecophysiological models will increase fire risk through decreased hydration and subsequent increased flammability of the species.
The following values have no corresponding Zotero field: pub-location: 150 OXFORD ST, PO BOX 1139, COLLINGWOOD, VICTORIA 3066, AUSTRALIA publisher: CSIRO PUBLISHING
Keywords: Arbutus unedo; Cistus albidus; emission and content of volatile compounds; Erica multiflora; Globularia alypum; phillyrea latifolia; Pinus halepensis; Pistacia lentiscus; Quercus ilex; Rosmarinus officinalis

Influence of water and terpenes on flammability in some dominant Mediterranean species - Alessio, G A; Penuelas, J; Llusia, J; Ogaya, R; Estiarte, M; De Lillis, M (INTERNATIONAL JOURNAL OF WILDLAND FIRE, 2008)
In the Mediterranean basin, fires are a major concern for forest and shrubland ecosystems. We studied flammability, its seasonality and its relationship with leaf moisture and volatile terpene content and emission in the dominant species of a Mediterranean shrubland and forest in Catalonia ( NE Iberian Peninsula). We measured temperatures and time elapsed between the three flammability phases: smoke, pyrolysis and flame, for four seasons. We sampled twice in spring because of an occasional drought period during this season. Flammability had a significant relationship with leaf hydration, in the shrubland and in the forest. Few and only weak correlations were found between terpene content and flammability. In the future, arid conditions projected by climatic and ecophysiological models will increase fire risk through decreased hydration and subsequent increased flammability of the species.
Keywords: Arbutus unedo; Cistus albidus; emission and content of volatile compounds; Erica multiflora; Globularia alypum; phillyrea latifolia; Pinus halepensis; Pistacia lentiscus; Quercus ilex; Rosmarinus officinalis